Uterine involution after term childbirth - Anwar N. Al- Bassam (مجلة كلية الطب, 2009)
Background: uterine involution is the process by which the postpartum uterus returning to its prepregnant state by the process of autolysis. The aim of the study is to fallow the uterine involution sonographicly during the first two weeks of puerperium and clinical correlation of several puerperal conditions was sought. Patients and methods: One hundred full term women were delivered in one of Baghdad hospital during a six month period were followed by serial sonogram during the first two weeks of the puerperal period to show the normal process of uterine regression in relation to several condition .The rate of uterine involution were shown as percentage drop in uterine volume at day (7) and day (14) compared to day (1). Results: 59 patient included in this project were delivered vaginally, and 41 patient delivered by emergency C/S. The mean percentage drop in uterine volume in vaginal delivery was 39.9% at 7 days postpartum & 62.7%at 14days postpartum and in those delivered by C/S was 27.9%at 7 days and 55.2 %at 14 days postpartum. 24 patients had an abnormal offensive lochia and high vaginal swab was positive for the presence of pathogenic organisms is 46% and negative in 54%inthe 7th postpartum day. The mean percentage drop in uterine size was faster in women delivered infant less than 4 kg.(37%drop) compared to those delivered infant more than 4 kg.(26% drop) in the 1st 7 days postpartum regardless to the mode of delivery but the body weight loses its effect in the 14th day postpartum. Conclusion:The uterine involution is faster in women delivered vaginally compared to those delivered by emergency C/S regardless to the weight of the newborn.The uterine involution is delayed in women delivered newborns weighing more than 4 kg. , also the uterine involution is delayed in women who are their high vaginal swab show presence of pathogenic organism. No correlation was found between breast feeding &rate of uterine involution.